Periphery Biomarkers for Objective Diagnosis of Cognitive Decline in Type 2 Diabetes Patients - Liu, Yanchao; Zhang, Shujuan; He, Benrong; Chen, Liangkai; Ke, Dan; Zhao, Shi; Zhang, Yao; Wei, Wei; Xu, Zhipeng; Xu, Zihui; Yin, Ying; Mo, Wen; et al. (Frontiers in Cell and Developmental Biology, 2021)
Abstract Type 2 diabetes (T2DM) is an independent risk factor of Alzheimer’s disease (AD), therefore, discerning who may be more vulnerable to AD is important for early intervention. This study was to identify periphery biomarkers for predicting cognitive decline in T2DM patients. Methods: 852 T2DM patients diagnosed by Petersen criterion were assigned randomly to the training and validation cohorts. Plasma β-amyloid (Aβ1-42/Aβ1-40), platelet glycogen synthase kinase-3β (GSK-3β), leucocyte ApoE genotypes, olfactory and cognitive functions were measured by ELISA, dot blot, RT-PCR, CCCRC and MMSE tests, respectively. Results: Elevated plasma Aβ1-42/Aβ1-40 is an independent risk factor of mild cognitive impairment (MCI) in T2DM patients. Combination of the elevated Aβ1-42/Aβ1-40, GSK-3β activation, ApoE4 genotype, olfactory decline and ageing could discriminate T2DM-MCI from T2DM-nMCI, with AUC of 0.869 and 0.867 in training and validation cohorts, respectively. Conclusions: The model could predict MCI in T2DM patients. Longitudinal studies will consummate the model for early diagnosis of AD.